Utilisation of incinerated sewage sludge ash as a matrix for cadmium stabilisation. Issue 1 (2nd January 2017) - Su, Minhua; Shih, Kaimin
ABSTRACT: This study investigates the feasibility of beneficially using two types of incinerated sewage sludge ash (ISSA) for cadmium stabilisation. The sewage sludge samples were collected from a secondary sewage treatment work (SSTW) and a chemically-enhanced primary sewage treatment works (CEPSTW). Prior to the cadmium immobilisation process, the collected sludge was pretreated at 900°C for 30 minutes. Both X-ray fluorescence (XRF) and X-ray diffraction (XRD) were employed to determine the elemental compositions and mineral phases of the ISSA. The results show that the ISSA contained a considerable amount of Si, Al and Fe, etc., offering the possibility to reuse the ISSA for the treatment of cadmium. To immobilise cadmium, cadmium oxide (CdO) was alternatively mixed with the ISSA with different molar ratios of Cd/Si. With a 950°C/3 hour treatment, cadmium was successfully incorporated into the Cd-Al-Si phase, the Cd-Si phase(s) and the Cd-Fe spinel. These product phases have high acid resistances, as revealed by a constant-pH leaching test (CPLT). The formation of the Cd-Al-Si phase, the Cd-Si phase(s) and the Cd-Fe spinel are highly influenced by the amount of cadmium presents in the treatment system. The success of utilising ISSA for cadmium stabilisation may provide a promising avenue for the sustainable management of the ISSA as well as the waste containing heavy metals.